Blended Learning: Altenatif Strategi Peningkatan Kompetensi Belajar Peserta Didik Pada Masa Pandemi Covid-19 di RA Al-Ghazali Medan Barat - Sitorus, Syahrul; Nurhanida, Nurhanida; Wahyuningsih, Sri; Tobing, Fitri Hasanah L. (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
This study aims to analyze (1) the application model of blended learning at RA Al-Ghazali Medan Barat, (2) various strategies for increasing student learning competence during the Covid-19 pandemic, (3) various obstacles faced in improving student learning competence. . This research uses qualitative research methods, with a case study approach. This research was conducted at RA Al-Ghazali Medan Barat, in which educators, school principals, students and parents became research informants. The results showed that blended learning at RA Al-Ghazali is a learning that combines face-to-face and online learning in its learning system. This comes as a response to the ongoing Covid-19 pandemic. The various alternatives in improving student learning competence are: (1) the application of student-centered learning strategies, (2) strengthening the role of parents as companions, (3) the application of active learning-based learning, (4) the use of multimedia-based learning media, ( 5) Time efficiency and learning atmosphere. As for the obstacles faced in improving learning competence (1) Network constraints, (2) Lack of cooperation between parents and teachers, (3) The occurrence of differences of opinion between teachers and parents.